2021
DOI: 10.1039/d1lc00192b
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying nanotherapeutic penetration using a hydrogel-based microsystem as a new 3D in vitro platform

Abstract: The huge gap between 2D in vitro assays used for drug screening, and the in vivo 3D-physiological environment hampered reliable predictions for the route and accumulation of nanotherapeutics in vivo....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“… 27 Therefore, a satisfactory penetration depth and uniform NP diffusion are usually required to maximize the therapeutic effects. We used a 3D MCTS model that simulates the complex situation of the tumor site 28 to evaluate the ability of the IGP@P NPs to penetrate into the tumor with the assistance of LIFU irradiation. In the absence of LIFU irradiation, we found that the red fluorescent DiI-labeled IGP@P NPs were mainly distributed on the surface of the 3D MCTSs, and only a small amount of the NPs penetrated into the model.…”
Section: Resultsmentioning
confidence: 99%
“… 27 Therefore, a satisfactory penetration depth and uniform NP diffusion are usually required to maximize the therapeutic effects. We used a 3D MCTS model that simulates the complex situation of the tumor site 28 to evaluate the ability of the IGP@P NPs to penetrate into the tumor with the assistance of LIFU irradiation. In the absence of LIFU irradiation, we found that the red fluorescent DiI-labeled IGP@P NPs were mainly distributed on the surface of the 3D MCTSs, and only a small amount of the NPs penetrated into the model.…”
Section: Resultsmentioning
confidence: 99%
“…While these particles have attracted great interest, the complexity of their design and release profiles has impeded their translation into clinical use [ 15 , 30 ]. Methodologies that can improve our understanding of how the biophysical properties of the nanoparticles impact their cellular uptake have potential to enrich existing methods for nanoparticle evaluation, to collectively advance nanoparticle research [ 5 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturing process has already been detailed in Goodarzi et al 23,24 . Briefly, 200µm diameter micro-wells were molded with 2% agarose solution over PDMS counter-moulds.…”
Section: Microfabricated Devicementioning
confidence: 99%
“…21 The proportion of CSCs within a given cell population derived from either tumor samples or in vitro cell cultures can therefore be evaluated by functional tests that are based on their capacity to survive as single cell and/or reconstitute a population of cancer cells in vitro 22 . Therefore, in order to provide time-resolved characterization of CSCs populations at individual cell level, we have generated data sets from LFBM time-lapses of patient-derived brain CSCs in suspension, cultured in micro-wells of a microfabricated chip recapitulating in this way classical stem cell culture conditions (Figure 1) 23,24 . This system can generate high-throughput images of micro-wells ( circa 15 micro-wells per second) and requires fast and accurate analysis of micro-wells content to assess cell fate.…”
Section: Introductionmentioning
confidence: 99%